2013
DOI: 10.3390/ijms14035198
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Symbiotic Efficiency of Medicago truncatula and Medicago sativa under Phosphorus Deficiency

Abstract: Phosphorus (P)-deficiency is a major abiotic stress that limits legume growth in many types of soils. The relationship between Medicago and Sinorhizobium, is known to be affected by different environmental conditions. Recent reports have shown that, in combination with S. meliloti 2011, Medicago truncatula had a lower symbiotic efficiency than Medicago sativa. However, little is known about how Medicago–Sinorhizobium is affected by P-deficiency at the whole-plant level. The objective of the present study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…S6) imply that the substantial accumulation of identified amino acids in McCP-31-induced nodules may be the result of the higher SNF capacity and N assimilation under low Pi conditions (Fig. 5A) (40). Indeed, the significant increase in total soluble protein content observed in McCP-31-induced nodules under low Pi treatment (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…S6) imply that the substantial accumulation of identified amino acids in McCP-31-induced nodules may be the result of the higher SNF capacity and N assimilation under low Pi conditions (Fig. 5A) (40). Indeed, the significant increase in total soluble protein content observed in McCP-31-induced nodules under low Pi treatment (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Plants engaged in symbiotic N 2 fixation are known to have high P demand (Vance et al ., 2003; Sulieman et al ., 2013). This is related to the high energy that is required for nitrogenase to function at a high level.…”
Section: Discussionmentioning
confidence: 99%
“…This premise was necessary for identifying the better symbiotic partner for M. truncatula between both strains, as well as characterizing the reasons for the suboptimal efficiency for M. truncatula × S. meliloti under low P supply. Indeed, little is known about how M. truncatula × S. meliloti is affected by P deficiency at the whole-plant level (Sulieman et al ., 2013). The present data revealed that under conditions of suboptimal P supply (1 μM P), the symbiotic performance of M. truncatula – S. meliloti 102F51 plants was more sensitively affected when compared with that derived from combination with S. meliloti 2011 (Tables 2, 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations